2022
DOI: 10.3389/froh.2021.832976
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Antimicrobial Activity of Dental Mesenchymal Stromal Cells: Is There Any Potential?

Abstract: Antimicrobial defense is an essential component of host-microbial homeostasis and contributes substantially to oral health maintenance. Dental mesenchymal stromal cells (MSCs) possess multilineage differentiation potential, immunomodulatory properties and play an important role in various processes like regeneration and disease progression. Recent studies show that dental MSCs might also be involved in antibacterial defense. This occurs by producing antimicrobial peptides or attracting professional phagocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Another past study showed that the direct effect of the LL-37 peptide was to cause enzyme mediated destruction of bacteria while the indirect effect was to regulate inflammatory markers [ 29 ]. In another study, the production and biochemical levels of cathelicidins were noted to be directly affected by the levels of inflammation and vitamin D [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another past study showed that the direct effect of the LL-37 peptide was to cause enzyme mediated destruction of bacteria while the indirect effect was to regulate inflammatory markers [ 29 ]. In another study, the production and biochemical levels of cathelicidins were noted to be directly affected by the levels of inflammation and vitamin D [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…They possess the capacity to interrupt the resistance bio lm and bacteria's thereby also decreasing the production of in ammatory markers [30].Similar study was conducted by to evaluate LL-37 levels in children, and showed that lower concentration of LL-37 were associated with high caries activity, even though it was not statistically signi cant, they clearly mention that LL-37 can be a prognostic marker and is a protective factor again caries in children, adolescents and adults [26].LL-37 has a potent effect on streptococcus mutans, and prevents it growth and colonization by carpet model, toroidal model and barrel stave model [31].The primary effect of these peptides are direct effect on enzymatic destruction of bacteria and indirect effect through in ammatory markers [32]. The production and biochemical levels of cathelicidins are directly affected by the in ammatory levels and vitamin D [33]. The interleukin 6 levels were increased in caries active group in comparison with caries free group even though it was not statistically signi cant, it can be due to the pro in ammatory function of these interleukins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the transfection of MSCs with AMP (regulated by chemical products). Bacteria, inflammatory cytokines, and vitamin D3 promote antibacterial effects and could also enhance regenerative processes [ 92 , 93 ]. In addition, the field of precision medicine, which includes prevention and treatment strategies, takes individual variables into account, thanks to the development of large-scale biological databases and computational tools that allow analyzing these data.…”
Section: Translational Applications Of Msc From the Oral Cavitymentioning
confidence: 99%
“…Following numerous studies, in vitro and in vivo, the effect of such cells depends on multiple factors, such as the tissue source of the MSCs, the experimental setting, and the type of preparation of the immune cells. In fact, cellular dialogue can not only influence the local immune response, but also extend to the systemic level, influencing the properties of both the innate and acquired immune systems [ 93 ]. It is important to keep in mind that DPSC and SHED from patients with systemic pathologies (immunological, diabetes, rheumatoid arthritis, etc.)…”
Section: Types Of Mesenchymal Stem Cells From the Oral Cavity (Dmsc I...mentioning
confidence: 99%
See 1 more Smart Citation